Synergistic Effects Of Polyphenon 60, Curcumin, And Ciprofloxacin In Nanoemulsion Systems Against Resistant Bacterial Strains (International Journal of Environmental Sciences, 2025)
Antibiotic resistance continues to be a major global health challenge, especially with the rise of multidrug-resistant (MDR) bacteria. This study investigates the synergistic effects of Polyphenon 60 (P60), Curcumin (CUR), and Ciprofloxacin (Cipro) encapsulated in nanoemulsions to enhance their antibacterial activities against drug-resistant uropathogenic bacterial strains. Nanoemulsions, which have demonstrated superior solubility, stability, and bioavailability properties, were developed to encapsulate both hydrophobic and hydrophilic drugs. The combined formulation of P60, CUR, and Cipro exhibited a significantly enhanced antibacterial activity compared to individual drugs. In vitro results, including MIC (Minimum Inhibitory Concentration) testing and Fractional Inhibitory Concentration (FIC) indices, demonstrated that the combination of these compounds showed a synergistic effect against both Gram-negative and Gram-positive bacteria. This synergy highlights the potential of using such formulations as alternative therapies to combat antibiotic-resistant infections, specifically in the treatment of urinary tract infections (UTIs).